STATICS ANALYSIS OF PLANAR TRUSSES STRUCTURE WITH FINITE ELEMENT SOFTWARE - Saputra, Hadi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2021)
A truss is a structure that is a combination of several slender members. The high performance of the truss structure has been the first effort. The advancement of the truss structure analysis is required. Traditionally, analysis of truss structure is usually done with joints or section methods. There are not secure to solve with the theoretical statically determinate. Otherwise, more advanced techniques are compulsory. This report aims to use the finite element methods software to learn the behavior of truss structures and to compare with the theoretical of statically determinate manual calculation. The result has been shown that both methods had been given the similarity results. It means that the finite element software (Abaqus student editions software) entirely accurate to be used to analyze the 2D-trusses structure. Hopely its can be used to solve other complex problems in construction analysis.